General Organization - Parmaxi, Antigoni (My University, 2026)
The seminar will explore the lessons learnt and reflect on the challenges that have arisen in the last 18 months regarding education and young people. Andria Zafirakou will introduce us to an educational environment where we will learn what we need to stop, continue or start doing in our classrooms, through these lessons. The seminar is open access and is addressed to professionals working in primary, secondary and tertiary education, freelancers in the field of education, students who will follow the field of learning and education, but also the wider public.